Pragmatic Peculiarities Of Anthroponyms And Anthortoponyms (Eurasian Journal of Learning and Academic Teaching, 2022)
This article investigates the characteristics of anthroponyms and anthroponyms, as well as providing information on anthroponyms. With examples, the characteristics of proper nouns are explained. The play's toponyms are primarily classified by the breadth of their meaning and the language to which they belong